Empathy Research Trends in Early Childhood Social-Emotional Development - Rika Purnamasari; Bunyamin Maftuh; Mupid Hidayat; Warlim Warlim; Juntika Nurihsan; Ace Suryadi; Yuwan Fijar Anugrah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the development of research on the character of empathy in the context of early childhood social-emotional development through a bibliometric approach. Data were obtained from scientific publications using the Publish or Perish application during the period 2016-2026. Bibliometric analysis was used with the help of VOS viewer software to analyze annual trends, dominant keywords, and the number of publications based on data collection on Google Scholar. Furthermore, the analysis results show differences in research publications in Indonesia from 2016 to 2026, which can be periodized as follows: 2016-2019 as a period of research focused on theory formation and instrument development, 2020-2023 as a period of contextualization and relationality, and 2024-2026 as a period focused on intervention. Furthermore, keyword mapping reveals the relationship between empathy and the social-emotional learning approach in early childhood education practices. These findings provide a comprehensive overview of scientific developments and identify opportunities for further research, particularly in the context of early childhood education in Indonesia. This study is expected to serve as a reference for researchers and practitioners in developing innovative and novel studies and practices for strengthening empathy in early childhood.